Cheminformatics-based screening and evaluation of phytochemicals as CDK2 inhibitors in colorectal cancer therapy - Nowshin Tabassum; Md. Ekram Hossan; Md. Mujahidul Islam; Mahmudul Hasan; Md Salamoon Islam; Sunjida Masud; Firoz Ahmed; Noimul Hasan Siddiquee (PLoS ONE, 2025)
Colorectal cancer (CRC) poses a significant global health issue. It ranks as the third most common type of cancer and the second leading cause of cancer-related deaths. Among the molecular factors driving its progression, cyclin-dependent kinase 2 (CDK2) plays a key role. CDK2 is a protein kinase essential for regulating the cell cycle, and its dysregulation is implicated in the development of various cancers, notably CRC. Fruquintinib is an already available drug against CRC. However, this study is being performed in search of better drug-like compounds. Some studies have shown that phytochemicals are less toxic and have fewer adverse effects than commercially available medications. With the vision of detecting CDK2 inhibitors, phytochemicals with anticancer activity can be used as alternatives to develop the drug candidate. Cheminformatics-based analysis is used for this purpose. This approach includes molecular docking, adsorption, distribution, metabolism, excretion/toxicity (ADME/T), post-docking molecular mechanism generalized born surface area (MM-GBSA), structural activity relationship (SAR), frontier molecular orbital (FMO), and molecular dynamics (MD) simulations. Molecular docking was employed to determine the binding strength of 4433 phytochemicals with anti-cancer properties sourced from the IMPPAT database. The top five candidates, CIDs-135438111, 6474893, 44257567, 10469828, and 353825, were selected based on their docking scores. Later, three lead compounds, CIDs-6474893, 10469828, and 135438111, were finalized depending on their favorable ADME/T profiles. All three selected pharmaceuticals demonstrated excellent post-dock MM-GBSA scores and HOMO-LUMO energy gaps, which served as confirmation of their efficacy and safety. The SAR analysis also revealed anti-mutagenic, antineoplastic, and apoptosis-inducing properties of the compounds. Finally, the rigidity of the protein-ligand complex structures was verified by MD simulations. Overall, the study suggests these three phytochemicals exhibit stronger binding and better pharmacological profiles than the control (fruquintinib), offering a promising direction for CRC treatment development.